Cambodian Youth Perspectives on Social and Educational Barriers: An exploratory case study in a rural border region - Tost, Jeremy; Spires, Bob; In, Sokleng (Journal of Interdisciplinary Studies in Education, 2019)
This case study examines these barriers using a questionnaire assessing the youth’s attitudes toward education (n = 50). Results indicated that poverty and the pressure to migrate for work remain significant barriers to educational attainment, despite the perceived benefits of education by youth and encouragement by families. Results revealed that inter-educational issues occur despite unclear prevalence, including negative pressures, physical and verbal abuse of students by teachers, teachers charging students fees, and government schools being comparatively less safe and encouraging than home and a local NGO school. These findings can be used to better tailor development aid targeting educational measures, particularly encouraging a shift from convincing rural Cambodians to value education to targeting the contextual barriers that exist.